Osteogenesis imperfecta type I: Second-trimester diagnosis and incidental identification of a dominant COL1A1 deletion mutation in the paucisymptomatic father - Chih-Ping Chen; Yi-Ning Su; Tung-Yao Chang; Schu-Rern Chern; Chen-Yu Chen; Jun-Wei Su; Wayseen Wang (Elsevier, 2012)
Objective: To present second-trimester ultrasound and molecular diagnosis for osteogenesis imperfecta (OI) type I in a female fetus and incidental identification of a dominant COL1A1 deletion mutation in her paucisymptomatic father. Case Report: A 30-year-old, primigravid woman was referred for genetic counseling in the second trimester because of bowing of the fetal lower limbs. She and her husband were non-consanguineous, and there was no family history of skeletal dysplasias. Prenatal ultrasound at 22 weeks of gestation revealed short and curved right femur and left tibia, and a short left fibula. The lengths of other long bones were normal. The husband was 158 cm tall, had blue sclerae, a history of habitual subluxation and dislocation of bilateral elbows and left knee, and an episode of left ulna fracture, and was not aware of his being affected with OI type I. The woman underwent amniocentesis. Cytogenetic analysis revealed a karyotype of 46,XX. Molecular analysis of the amniocytes revealed a heterozygous deletion mutation of c.1064_1068delCTGGT in exon 17 of the COL1A1 gene. By genetic testing the husband was found to carry the same mutation. Despite counseling of favorable outcome for OI type I with the parents, the woman elected to terminate the pregnancy. Postnatal skeletal X-ray findings were consistent with OI type I. Conclusion: Prenatal ultrasound diagnosis of mild forms of OI should include molecular analysis of type I collagen genes in both fetus and parents. Molecular genetic analysis of the family may incidentally identify a collagen gene mutation in the paucisymptomatic affected parent.